Accuracy of Intraoral Scanner for Recording Completely Edentulous Arches-A Systematic Review - Gunjan Srivastava; Subrat Kumar Padhiary; Neeta Mohanty; Pedro Molinero-Mourelle; Najla Chebib (MDPI AG, 2023)
Scanning edentulous arches during complete denture fabrication is a crucial step; however, the quality of the resulting digital scan is still questionable. The purpose of this study is to systematically review studies (both clinical and in vitro) and determine whether intraoral scanners have clinically acceptable accuracy when recording completely edentulous arches for the fabrication of removable complete dentures. An electronic search in medical databases like PubMed, Scopus, and Web of Science (WOS), using a combination of relevant keywords, retrieved 334 articles. After full-text evaluation, twelve articles fulfilled the inclusion criteria for this review (eight clinical studies and four in vitro studies). A quality analysis of the included studies was carried out using the QUADAS-2 tool. The accuracy values varied between different intraoral scanners. Different regions of the edentulous arches showed differences in trueness and precision values in both in vitro and clinical studies. Peripheral borders, the inner seal, and poorly traceable structures like the soft palate showed maximum discrepancies. The accuracy of intraoral scanners in recording clear anatomic landmarks like hard tissues with attached mucosa was comparable to conventional edentulous arch impressions. However, higher discrepancies were recorded when digitizing mobile and poorly traceable structures. Intraoral scanners can be used to digitize denture-bearing areas, but the interpretation of the peripheral border and the soft palate should be carefully carried out.